Maser polarization simulation in the circumstellar envelope of an evolving star. Issue 1 (1st January 2023) - Phetra, M; Gray, Malcolm D; Asanok, K; Kramer, Busaba H; Sugiyama, K; Chanapote, T; Nuntiyakul, W
Abstract: An important phenomenon in a pulsing AGB (Asymptotic Giant Branch) star is the variability of its circumstellar envelope. The study of stimulated radiation called SiO maser (microwave amplification by stimulated emission of radiation) in the inner edge of the envelope shows fluctuations in polarization during the stellar pulsation period which is caused by the unstable magnetic field around the AGB star and needs to be investigated in order to understand it. We simulate the maser signal and polarization by using a computer code to describe the circumstellar envelope of the AGB star for comparison with the observations. The methods, i) Generate the energy transition of the stimulation matrix ii) Simulate the first stimulation from an electric field background iii) Convert the radiation to the frequency domain by using Fourier transform iv) Simulate the observation by amplifying radiation along a line of sight within the medium toward an observation position. At this stage, we set the tubular maser cloud with a constant magnetic field strength toward the observer. The program can simulate the maser signal and polarization, brighter when stimulating with a longer medium; the simulated polarization agrees well with expectations for this magnetic field orientation. Further works need to be carried out by testing this program with many cases to explain the obtained data from actual observations.